THE EFFECT OF MERGERS AND ACQUISITIONS ON ABNORMAL RETURN: CASE STUDY OF 46 LISTED COMPANIES IN INDONESIA STOCK EX- CHANGE (IDX) FROM 2010-2016 - Fadlitama, Luthfie; Adawiyah, Wardatul (Emerging Markets : Business and Management Studies Journal, 2017)
This research aims to analyze whether there is a significant difference of abnormal returns due to the occurrence of mergers and acquisitions activity in which affect the wealth value of the shareholders and to determine the return of the shareholders after mergers and acquisition proportion is announced. In order to calculate the abnormal returns, this research uses two different approach; market model and market adjusted modelEvent study methodology is used to determine the abnormal return using market model and market adjusted model over period 10 days before and 10 days after consummation of mergers and acquisitions. The result of this study shows that significant abnormal returns before and after mergers and acquisitions activity is not exist (accept H0). Furthermore, when proportion (mergers and acquisitions of more than 50% and less than 50% of target interests) is used to analyze the return for shareholders, theresults show that mergers and acquisitions of more than 50% target interests generate positive return for shareholders of acquiring and target firms (reject H0). In mergers and acquisitions of less than 50% only accrue positive return for shareholders of acquiring firms (reject H0) while shareholders of target firms suffer negative return (accept H0)